Know your farmer: Ancient origins and multiple independent domestications of ambrosia beetle fungal cultivars. Issue 8 (23rd November 2017) - Vanderpool, Dan; Bracewell, Ryan R.; McCutcheon, John P.
Abstract: Bark and ambrosia beetles are highly specialized weevils (Curculionidae) that have established diverse symbioses with fungi, most often from the order Ophiostomatales (Ascomycota, Sordariomycetes). The two types of beetles are distinguished by their feeding habits and intimacy of interactions with their symbiotic fungi. The tree tissue diet of bark beetles is facilitated by fungi, while ambrosia beetles feed solely on fungi that they farm. The farming life history strategy requires domestication of a fungus, which the beetles consume as their sole food source. Ambrosia beetles in the subfamily Platypodinae originated in the mid‐Cretaceous (119–88 Ma) and are the oldest known group of farming insects. However, attempts to resolve phylogenetic relationships and the timing of domestication events for fungal cultivars have been largely inconclusive. We sequenced the genomes of 12 ambrosia beetle fungal cultivars and bark beetle associates, including the devastating laurel wilt pathogen, Raffaelea lauricola, to estimate a robust phylogeny of the Ophiostomatales. We find evidence for contemporaneous diversification of the beetles and their associated fungi, followed by three independent domestication events of the ambrosia fungi genus Raffaelea . We estimate the first domestication of an Ophiostomatales fungus occurred ~86 Ma, 25 million years earlier than prior estimates and in close agreement with the estimated age of farming in the Platypodinae (96 Ma). Comparisons of the timing of fungal domestication events with the timing of beetle radiations support the hypothesis that the first large beetle radiations may have spread domesticated "ambrosia" fungi to other fungi‐associated beetle groups, perhaps facilitating the evolution of new farming lineages.